Insects, Insecticides and Hormesis: Evidence and Considerations for Study - G. Christopher Cutler (SAGE Publishing, 2013)
Insects are ubiquitous, crucial components of almost all terrestrial and fresh water ecosystems. In agricultural settings they are subjected to, intentionally or unintentionally, an array of synthetic pesticides and other chemical stressors. These ecological underpinnings, the amenability of insects to laboratory and field experiments, and our strong knowledgebase in insecticide toxicology, make the insect-insecticide model an excellent one to study many questions surrounding hormesis. Moreover, there is practical importance for agriculture with evidence of pest population growth being accelerated by insecticide hormesis. Nevertheless, insects have been underutilized in studies of hormesis. Where hormesis hypotheses have been tested, results clearly demonstrate stimulatory effects on multiple taxa as measured through several biological endpoints, both at individual and population levels. However, many basic questions are outstanding given the myriad of chemicals, responses, and ecological interactions that are likely to occur.